Gasification of biomass with CO2 and H2O mixtures in a catalytic fluidised bed - Jeremiáš, M.; Pohořelý, M.; Svoboda, K.; Manovic, Vasilije; Anthony, Edward J.; Skoblia, S.; Beňo, Z.; Šyc, M. (Elsevier, 2017)
Steam can be fully or partially substituted by CO2 as a gasification agent. This substitution affects producer gas composition, char conversion and in-situ tar reforming. Here, wood chips were gasified in a spouting fluidised bed using silica sand and catalytic dolomitic lime as the bed material at 850 °C. The use of a gasifying agent composed of CO2 and H2O was compared to the use of CO2 or H2O alone. It was found that mixtures of CO2 and H2O as the gasifying agent improve char conversion, and that the combined gasification agents are very effective in ensuring the decomposition/destruction of tars when lime based materials are used in the fluidised bed.
Keywords: Fluidised bed; Gasification; Catalyst; Dolomite; Limestone; Synergistic effect